PHYSICAL AND CHEMICAL CHARACTERISTICS OF RAWAI AREA IN DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Tri Hidayati; T. Ersti Yulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRAKThis research wes conducted on agustus , 2014 in Desa Bantan TengahKecamatan Bantan Kabupaten Bengkalis. This study aimed to anderstand thephysical and chemical parameters on longline fishing ground. There were 3sampling points, water quality parameter were measured everyday for 10 daysperiod. analytical description was used to evaluate the relationship betweenlongline catches and the environmental factors such as dissolved temperatur,salinity, current speed, depth of water, brigthness and pH, on this research bydescriptive analysis.Everage weigth of catch is 1.3 kg, consist of Silver Conger (muarenesoxcinareus), kuro (Eleutheronema sp), Red Snapper (Lutjanus sp), Deep Leatherskin(Scomberoides tala), Barracuda (Sphyraena sp), Gerot-Gerot (Pamadaysmaculates). Results shown that enviromental parameters as follow dissolvedtemperature 27 0C – 29 0C, salinity 21 – 30 ‰, current speed 0,15 m/s – 1,60 m/s,brigthness 1.20 m -2,20 m, depth of water 20 m – 50 m, and (pH) 7-8.Keywords :longline, physical and chemical waters parameter, fishing ground